Įstrigusi obturatorinė išvarža 49-erių metų moteriai: atvejo aprašymas ir literatūros apžvalga - Markevičius, Marius; Lunevičius, Raimundas; Markovas, Vitalijus; Stanaitis, Juozas (Lietuvos chirurgija, 2010)
Marius Markevičius, Raimundas Lunevičius, Vitalijus Markovas, Juozas StanaitisVilnius University, Center of General Surgery, Vilnius University Emergency Hospital,Šiltnamių str. 29, LT-04139 Vilnius, LithuaniaEl. paštas: marijuss@gmail.comIncarcerated obturator hernia in 49 year old women: a case report and review of the literatureMarius Markevičius, Raimundas Lunevičius, Vitalijus Markovas, Juozas StanaitisVilnius University, Center of General Surgery, Vilnius University Emergency Hospital,Šiltnamių str. 29, LT-04139 Vilnius, LithuaniaE-mail: marijuss@gmail.comIntroduction Incarcerated obturator hernia is a rare cause of bowel obstruction. This case report aimed to review the diagnosis and management of obturator hernia by describing the anatomy, clinical presentation, diagnostic modalities, and predisposing factors.Case presentation A 49-year-old woman presented to emergency department with progressive spastic abdominal pain, vomiting, abdomen enlargement, and tenesmus. One month before this episode she was diagnosed a carcinoma of the cervix uteri which was defined as T1b N1 M0 G2. She has undergone a curative R0 type surgery and adjuvant chemoradiation. There were no pelvic abnormalities described in the operative protocol. She lost 20 kg in two years. Because of ineffective conservative treatment, progression of acute bowel obstruction and signs of local peritonitis, she underwent an urgent curative laparotomy. It was confirmed that a loop of ileum was incarcerated and irreducible in the canal of right side of pelvis that suited to obturatoric foramen.Conclusion Rarity of such a condition makes great difficulties in diagnosing it. CT is needed to recognize obturator hernia in early stages before its incarceration. Significant lost weight (> 20 kg), and adjuvant chemoradiotherapy were most possible predisposing risk factors for right obturator hernia in 49 years old female.Keywords: obturator hernia, strangulated hernia, risk factors, laparoscopy, laparotomy.